Analisis Asbāb Al-Wurūd: Pendekatan Al-Jam'u dalam Memahami Hadis Tarku Al-Tazayyun - Akbar, Raabiul (Universitas Islam Negeri Alauddin, 2024)
This article explores the Asbab al-Wurud (reasons for the revelation of hadiths) in the context of Hadith Tazayyun through the al-Jam'u approach. The research aims to understand the interpretations of hadiths related to Tazayyun by integrating various perspectives and contexts. The methodology involves the analysis of hadith texts, a review of related literature, and an understanding of the historical and social contexts of the hadiths. The findings suggest that the al-Jam'u approach allows for a more holistic and relevant understanding of the Hadith Tazayyun, which is important for comprehending contemporary dynamics in Muslim societies.